Evaluating The Black-Scholes Option Pricing Model And Possible Option Pricing Alternative Using Market Data - Poon, Desmond Hin Lun (2009)
This project investigates the underlying properties of the Black-Scholes option pricing model and unveils some of its limitations. We investigate its characteristics by employing historical S&P500 data on a number of options transactions and evaluate its assumptions in the light of market data .